Localised effects of sparse natural tree colonisation on soil physicochemical properties - Naomi C. Housego; Thomas C. Parker; Lorna E. Street; Elena I. Vanguelova; Ruth J. Mitchell (Trees, 2026)
Tree establishment via natural colonisation is increasing globally, due to treeline expansion under climate change, and changing land management practices, such as reduced grazing pressure, land abandonment, and initiatives to increase tree cover such as restoration and rewilding. Natural colonisation of organo-mineral soils at high densities is associated with altered soil physicochemical properties, with consequences for ecosystem services such as soil carbon stocks, biodiversity, and hydrology. But whether sparse natural colonisation of organo-mineral soils has similar effects on soil physicochemical properties to dense natural colonisation is not known. To investigate the effects of sparse natural colonisation on organo-mineral soils, we measured soil physicochemical properties at increasing distances up to 8 metres from single, native ( Pinus sylvestris L. or Betula spp.) naturally colonised trees in Cairngorms, Scotland, UK. Distance from single, native, naturally colonised trees was associated with increased soil moisture and decreased carbon-to-nitrogen and carbon-to-phosphorus ratios, but not associated with changes in bulk density, decomposition rates, or pH, in the organic horizon of organo-mineral soils. Sparse natural colonisation (in this study, 43 trees ha − 1 ) of organo-mineral soils has some, localised effects on the physicochemical properties of the organic horizon, which might affect biodiversity and hydrology in patches around trees. These effects did not extend beyond 2 metres distance from the trees. This suggests that early, sparse tree colonisation has minimal impacts on soil physicochemical properties at the ecosystem scale.